Terror Attacks Increase the Risk of Vascular Injuries - Heldenberg, Eitan; Givon, Adi; Simon, Daniel; Bass, Arie; Almogy, Gidon; Peleg, Kobi (Frontiers in Public Health, 2014)
Objectives: Extensive literature exists about military trauma as opposed to the very limited literature regarding terror-related civilian trauma. However, terror-related vascular trauma (VT), as a unique type of injury, is yet to be addressed. Methods: A retrospective analysis of the Israeli National Trauma Registry was performed. All patients in the registry from 09/2000 to 12/2005 were included. The subgroup of patients with documented VT (N = 1,545) was analyzed and further subdivided into those suffering from terror-related vascular trauma (TVT) and non-terror-related vascular trauma (NTVT). Both groups were analyzed according to mechanism of trauma, type and severity of injury and treatment. Results: Out of 2,446 terror-related trauma admissions, 243 sustained TVT (9.9%) compared to 1302 VT patients from non-terror trauma (1.1%). TVT injuries tend to be more complex and most patients were operated on. Intensive care unit admissions and hospital length of stay was higher in the TVT group. Penetrating trauma was the prominent cause of injury among the TVT group. TVT group had a higher proportion of patients with severe injuries (ISS ≥ 16) and mortality. Thorax injuries were more frequent in the TVT group. Extremity injuries were the most prevalent vascular injuries in both groups; however NTVT group had more upper extremity injuries, while the TVT group had significantly much lower extremity injuries. Conclusion: Vascular injuries are remarkably more common among terror attack victims than among non-terror trauma victims and the injuries of terror casualties tend to be more complex. The presence of a vascular surgeon will ensure a comprehensive clinical care.